2023
DOI: 10.3390/en16093910
|View full text |Cite
|
Sign up to set email alerts
|

Balance and Energy Use of Biogas in Poland: Prospects and Directions of Development for the Circular Economy

Abstract: The production of biogas from biodegradable waste generated in all sectors of the economy in Poland is a key issue for the diversification of energy sources and climate neutrality. The biogas balances presented in the literature based on bio-waste often contain overly optimistic data, which in reality only represent the theoretical potential of biogas in Poland. The pragmatic approach presented in this study fills a gap in research by presenting a technical balance of biogas (real potential) that can be realis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…LFG was examined by Carriero et al [31], Ciuła et al [32], Garcia et al [33], Przydatek i Ci ągło [34], Przydatek et al [35], and Njoku et al [36]. Scientists from various countries have shown that landfill sites are a major source of greenhouse gas (GHG) emissions [37].…”
Section: Introductionmentioning
confidence: 99%
“…LFG was examined by Carriero et al [31], Ciuła et al [32], Garcia et al [33], Przydatek i Ci ągło [34], Przydatek et al [35], and Njoku et al [36]. Scientists from various countries have shown that landfill sites are a major source of greenhouse gas (GHG) emissions [37].…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of installations are also currently being upgraded for biomethane production [17,18]. The situation is different in other EU countries, such as Poland, where the biogas installation market is at a stage of dynamic growth and development [19]. It is this continuous development of the biogas sector that is associated with the generation of significant amounts of digestate pulp, requiring management.…”
Section: Introductionmentioning
confidence: 99%